FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS DENGAN FIRM SIZE SEBAGAI MODERASI - Seraphine, Adeline; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to prove in real terms what effect liquidity, leverage, sales growth have on financial distress moderated by firm size in tourism sector companies listed on the Indonesia Stock Exchange companies listed on the Indonesia Stock Exchange for the periode 2020-2022. This study used 16 samples of companies selected by purposive sampling and the the data was managed with EViews version 12th. The results obtained from this study, namely liquidity has a positive effect on financial distress, while leverage has a negative effect on financial distress, while sales growth does not have a significant effect on financial distress. The implications obtained are used as input for companies to project financial distress so that they can prepare appropriate actions.